Utilization of Phototrophic Bacteria to Enhance Carbon Sequestration in Rice Paddy - Alyssa Katsuyama Wang; Kun-Yi Kao; Yang-Cheng Kuo; Rey-May Liou (Engineering Proceedings)
Rice paddies are a major source of agricultural greenhouse gas emissions, primarily caused by the proliferation of anaerobic, methanogenic bacteria during prolonged inundation. Phototrophic bacteria utilize light energy for metabolism and are potential candidates for carbon and nitrogen fixation, and reduction of methane gas emissions. We investigated the effect of applying the phototrophic bacterium Rhodopseudomonas palustris (PNSB) during the cropping period on soil organic carbon (SOC) and methane emissions for second-crop rice in the Tainan Guantian region. In the experimental group, PNSB was applied five times during the rice cultivation period. Compared to the control group, the experimental group demonstrated a significant reduction in methane emissions, especially in the tillering stage, where emissions averaged 37.26 ± 12.97 g-CH4/m2/season compared to 49.48 ± 25.06 g-CH4/m2/season of the control group. Over the entire growing season, the experimental group reduced the emission of 3.05 Mg·CO2e/ha. Additionally, administering PNSB improved soil carbon sequestration, from 4.89 tons-C/ha in the control group to 17.45 tons-C/ha. The phototrophic bacterium PNSB was beneficial for soil carbon sequestration and reducing greenhouse gas emissions. However, further research is required to optimize the methodology of applying phototrophic bacteria for agricultural purposes.